Mechanisms and Dynamics of Mineral Dissolution: A New Kinetic Monte Carlo Model. Issue 10 (26th August 2019) - Martin, Pablo; Manzano, Hegoi; Dolado, Jorge S.
Abstract: Mineral dissolution is a fundamental process in geochemistry and materials science. It is controlled by the complex interplay of atomic level mechanisms like adatoms and terraces removal, pit opening, and spontaneous vacancy creation that can be gradually activated at different energies. Though the development of a comprehensive atomistic model is key to go deeper into the understanding of this phenomenon, existing models have failed to reproduce the abrupt dependence of the dissolution rate with the Gibbs free energy ( Δ G ). Herein, a new atomistic kinetic Monte Carlo (KMC) model is presented, which, invoking the microscopic reversibility of chemical reactions, captures the experimentally observed sigmoid dependence of the dissolution rate and provides new insights on the concomitant dissolution mechanisms. As a salient result, the model predicts the possible existence of unreported close‐to‐equilibrium dissolution modes where spontaneous vacancies creation and pit opening can occur before adatom and terrace removal. Abstract : Mineral dissolution is controlled by the complex interplay of atomic level mechanisms like adatoms removal, pit opening, or spontaneous vacancy creations. Herein a new atomistic kinetic Monte Carlo model is presented that captures for the first time the experimentally observed sigmoid dependence of the dissolution rate with the Gibbs free energy and provides new insights on the concomitant dissolution mechanisms.